Deixis Used Jo March In Little Women Movie - Febriana Margareta; Dwianggi Puspa Kinanti; arini hidayah (JELLE : Journal Of English Literature, Linguistics, and Education, 2022)
The title of this research is deixis which is used by Jo March in the film Little Women. This study focuses on deixis using the theory of Levinson in the film Little Women. The object of this study is the utterances delivered by Jo March as the main character in the film Little Women. First, this study aims to explain the kinds of deixis used by Jo March as the main role in the film Little Women. Second, this study aims to explain the reference to the word deixis used by Jo March as the main role in the film Little Women. This research method used by researchers is a qualitative descriptive method. The research data was taken from the film Little Women, directed by Greta Gerwig and written by Greta Gerwig based on the novel Little Women by Louisa May Alcott. This film originated from America in 2019. The results showed that there were 352 speech data containing deixis. From these data, there are three types of deixis studied. From these data, there were 308 person deixis, 20 place deixis, and 24 time deixis. The deixis phrase that is often used by Jo March is the I expression which refers to Jo which is included in the singular first person deixis (singular first person deixis). There are 120 data for expression I. Meanwhile, the reference most often used by speakers themselves is 308 data.